Endogenous electric fields as guiding cue for cell migration - Funk, Richard H. W. (Frontiers in Physiology, 2015)
This review covers two topics: (1) “membrane potential of low magnitude and related electric fields (bioelectricity)” and (2) “cell migration under the guiding cue of electric fields (EF).”Membrane potentials for this “bioelectricity” arise from the segregation of charges by special molecular machines (pumps, transporters, ion channels) situated within the plasma membrane of each cell type (including eukaryotic non-neural animal cells). The arising patterns of ion gradients direct many cell- and molecular biological processes such as embryogenesis, wound healing, regeneration. Furthermore, EF are important as guiding cues for cell migration and are often overriding chemical or topographic cues. In osteoblasts, for instance, the directional information of EF is captured by charged transporters on the cell membrane and transferred into signaling mechanisms that modulate the cytoskeleton and motor proteins. This results in a persistent directional migration along an EF guiding cue. As an outlook, we discuss questions concerning the fluctuation of EF and the frequencies and mapping of the “electric” interior of the cell. Another exciting topic for further research is the modeling of field concepts for such distant, non-chemical cellular interactions.